2014
DOI: 10.2169/internalmedicine.53.1403
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Glucose Level Increased in Parallel with the Heart Rate Following Cilostazol Administration in Three Diabetic Patients

Abstract: Cilostazol, a phosphodiesterase III inhibitor, is known to increase the heart rate; however, its effects on glucose metabolism remain unclear. We observed that the blood glucose level varied in parallel with the heart rate immediately after starting or stopping cilostazol therapy in three patients with type 2 diabetes. This finding indicates that cilostazol induces hyperglycemia and tachycardia in a portion of diabetic patients, presumably via similar pharmacological effects on different organs. Much more atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Serious adverse reactions include atrial fibrillation, cardiac arrest, myocardial infarction, and ventricular tachycardia, as well as bleeding and hemorrha-ging [27]. In a case report including three patients, a potential relationship between cilostazol-induced tachycardia and hyperglycemia was observed [28]. All three patients had a past medical history of type 2 diabetes and were admitted for cerebral infarction.…”
Section: Adverse Reactionsmentioning
confidence: 99%
“…Serious adverse reactions include atrial fibrillation, cardiac arrest, myocardial infarction, and ventricular tachycardia, as well as bleeding and hemorrha-ging [27]. In a case report including three patients, a potential relationship between cilostazol-induced tachycardia and hyperglycemia was observed [28]. All three patients had a past medical history of type 2 diabetes and were admitted for cerebral infarction.…”
Section: Adverse Reactionsmentioning
confidence: 99%
“…There exists concern that PTX might exert a negative impact on glycemic control in patients with diabetes. Previous studies have shown that PDE3,4 inhibitors enhance both glycogenolysis and gluconeogenesis in hepatocytes isolated from fasted rats [ 97 ], and the blood glucose level increases following the administration of cilostazol, a PDE3 inhibitor, in three patients with type 2 diabetes [ 98 ]. More recently, however, PDE4 inhibitors have been shown to improve glucose homeostasis in diabetic mice [ 99 ] and human patients [ 100 ], likely via enhancing the secretion of cAMP-mediated glucagon-like peptide 1 [ 99 ].…”
Section: Main Textmentioning
confidence: 99%